Biomonitoring of atmospheric lead (Pb) pollutants using Sphagnum moss in Bantay, Ilocos Sur, Philippines - Dalupang, Xander Paul P.; Matias, Hannah Ashley N.; Rivera, Monique Louriz D.; Viz, Jerick A. (2023)
Lead (Pb) pollution is a serious environmental and public health concern. In this study, we used Sphagnum moss bags to biomonitor lead particulates in gasoline stations and mechanic shops in Bantay, Ilocos Sur, Philippines. Lacking an air monitoring station in the municipality, this is the first study to use standard moss biomonitoring to detect atmospheric lead particulates in Ilocos Sur. Using atomic absorption spectroscopy, the moss bags were analyzed after 54 d of exposure. Results showed that the moss bags had accumulated lead – with mean concentrations of 2.1067 ppm in Area 1, 1.5547 ppm in Area 2, and 3.0733 ppm in Area 3. Area 3 had the highest loading values (92–95%), with a significant difference (P > 0.05) in lead content from the control pre-exposure (0.20 ppm). All calculated concentrations were higher than the standards of the Philippine Clean Air Act (0.000164 ppm). This result places the municipality of Bantay at possible risk of atmospheric lead pollution and, thus, highly encourages the creation of policies or initiatives to prevent further risks. Using Pearson’s correlation coefficient, the study also found that the loading values of the moss bags correlated with the station's temperature and humidity, as well as the moss’ hyaline pore size and density. Thus, these results suggest that Sphagnum moss can be a useful low-cost tool for biomonitoring lead pollution and that the environmental factors (temperature and humidity) and moss’ ultrastructures (hyaline pore size and density) may influence the bioaccumulation of lead in moss.
Keywords: Lead; Air pollution monitoring; Air pollution; Philippine Mosses; Heavy metal contamination